NILAI PERUSAHAAN: STUDI EMPIRIS FAKTOR-FAKTOR YANG MEMPENGARUHI - ARWINA KARMUDIANDRI; MERRY ADITA CHANDRA (Media Bisnis, 2021)
The purpose of this research is to analyze factors influencing firm value. The independen variable are investment opportunity, dividen policy, managerial ownership, financial leverage, profitability, firm size, board of indepedent commissioner, audit comittee. Population of this research is non-financial companies which are listed in Indonesia Stock Exchange from 2015 to 2017. The sample of this research are selected by using purposive sampling method, and 198 datas are taken. Data were analyzed using multiple regression method. The result of this research shows that financial leverage, profitability and board of independent commissioner have influence to firm value, whereas investment opportunity, dividen policy managerial ownership, firm size and audit comittee do not have influence to firm value.